2008
DOI: 10.1038/sc.2008.114
|View full text |Cite
|
Sign up to set email alerts
|

More than looking good: Impact on quality of life moderates the relationship between functional body image and physical activity in men with SCI

Abstract: Study design: Cross-sectional. Objectives: To examine the relationship between body image and leisure time physical activity (LTPA) among men with spinal cord injury (SCI). Specifically, to examine the moderating function of the perceived impact of body image on quality of life (QOL). Setting: Ontario, Canada. Methods: Men with SCI (N ¼ 50, 50% paraplegic) reported, (a) their functional and appearance body image (Adult Body Satisfaction Questionnaire), (b) their perceived impact of body image on QOL and (c) LT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 17 publications
(17 reference statements)
2
10
1
Order By: Relevance
“…It is possible that functional dissatisfaction may motivate some women to engage in LTPA. 9 Body image disturbance should be addressed in the years most proximal to injury onset as satisfaction with appearance and function may improve with time following injury. Future research should examine appearance and functional aspects of body image within Cash's model.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that functional dissatisfaction may motivate some women to engage in LTPA. 9 Body image disturbance should be addressed in the years most proximal to injury onset as satisfaction with appearance and function may improve with time following injury. Future research should examine appearance and functional aspects of body image within Cash's model.…”
Section: Discussionmentioning
confidence: 99%
“…Women with spinal cord injury in Bassett et al’s (2009) study were slightly dissatisfied with their appearance and slightly satisfied with their function. Meanwhile, in another study by Bassett and Martin Ginis (2009) among men with spinal cord injury, the men indicated overall satisfaction with appearance and function. The authors proposed that this may have been due to the men lowering their appearance and functional standards following their injury by shifting value away from physical qualities or changing the reference group (to other men with spinal cord injury).…”
mentioning
confidence: 94%
“…8 Most of the studies into body image of people with SCI focus on physical characteristics and/or physical activity. 3,4,[9][10][11][12][13][14][15] From these studies it becomes clear that SCI has consequences for the way people with SCI perceive oneself and interact with their surroundings, including potential partners. 4,10,12,13 Other studies suggest that the satisfaction with the body improves over the years after SCI.…”
Section: Introductionmentioning
confidence: 99%
“…11 Some studies found that the satisfaction with appearance after SCI was not different from a reference group. 9,14 One way to study body image from a cognitive behavioral point of view is to explore how people experience the relationship between their body and self. According to Bode, 16 this experience consists of two different aspects, namely Alienation and Harmony.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation